Using drawings as a means of summarizing reading passages in a university English reading classroom / Rofiza Aboo Bakar, Hairul Nizam Ismail and Aswati Hamzah - Rofiza Aboo Bakar; Hairul Nizam Ismail; Aswati Hamzah (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2010)
It has been noted that many university students do not know about strategies to summarize or organize information gained from their article reading. The aims of this research are to examine the accuracy of university students' drawings as summaries and their perceptions of drawing as a strategy to summarize reading articles in an English reading class. The study involves 19 students, aged between 19 to 20 years old, from the Food Service and Culinary courses in a Malaysian public university. Using newspaper reports, students first read the articles and after which they draw pictures to summarize the newspaper reports. The drawings cum the summaries are assessed by five experienced English lecturers using a scoring guide for drawings. The analysis showed that over 80% of the drawings were marked as accurate summaries of the newspaper articles. Through interviews, the study also revealed that students showed positive perception about drawing as it allowed them to make meanings through images and tap on their creative mind. It was also observed that the students were delighted and attentive in finishing the assignments. Drawing appeared to have the potential to be used as a summarizing strategy in a university English reading classroom.